Efektivitas Penyelenggaraan Program Pelatihan di UPT Balai Latihan Kerja Kabupaten Situbondo - Purwaningtyas, Gita Dewi; Helpiastuti, Selfi Budi; Rohman, Hermanto (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2022)
This study aims to describe and analyze the effectiveness of management of technical education and training for state civil servants in Situbondo Regency. Considering that the state civil servants is a public servant whose duty is to serve the entire community, they are required to always develop their competence through the management of technical education and training. Employment agency and human resources development as the organizer of technical education and training has held various kinds of technical education and training, one of which is the management of technical education and training of goods management. This type of research is descriptive qualitative. The focus of the research is the effectiveness of the management of technical education and training for the state civil servants based on four stages of Kirckpatrick consisting of reactions, learning, behavior, and results. Data collection techniques using interviews, observation and documentation, while the data sources used are the main data sources and additional data sources. The results showed that the management of technical education and training conducted by employment agency and human resources development was effective. This is known through 4 stages of Kirckpatrick which received positive responses from education and training participants and teaching staff. Keywords: Effectiveness, Technical Training, State Civil Servants